Channa striatus in inflammatory conditions: A systematic review - Lee, Vanessa Lin Lin; Choo, Brandon Kar Meng; Norazit, Anwar; Noor, Suzita Mohd; Shaikh, Mohd Farooq (Frontiers in Pharmacology, 2022)
Channa striatus (CS), or snakehead murrel, is an obligate air-breathing freshwater fish. Besides its wound healing properties, CS has also been reported to exhibit anti-inflammatory effects in multiple studies. While there are anti-inflammatory medications such as nonsteroidal anti-inflammatory drugs (NSAIDs), their long-term use is associated with an increased risk of peptic ulcers, acute renal failure, stroke, and myocardial infarction. Thus, it is essential to look at natural methods such as CS extract. While there is an abundant number of investigative studies on the inflammatory properties of CS, the quality of these studies has not been evaluated effectively. Thus, this review aims to summarise, evaluate, and critically appraise currently available literature regarding the anti-inflammatory properties of CS extract. This is done by performing a search using four databases, namely Google Scholar, Embase via Elsevier, Scopus, and Web of Science, with the following terms: Channa striatus AND inflammation. From our review, CS has been experimentally shown to positively affect inflammatory conditions such as gastric ulcers, dermatitis, osteoarthritis, and allergic rhinitis. Beneficial effects were also found on inflammation in the presence of tuberculosis and in situations that involve inflammation, such as wound healing. While CS clearly has potential for treating inflammatory conditions, much work needs to be done on identifying and isolating the active constituents before exact mechanisms of action can be worked out to develop future anti-inflammatory medications.